Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Pegawai Pada Pelabuhan Perikanan Samudera Bitung - Christiany Shyntia Tombokan; Ferderik Mario Manikome (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine (1) the influence of work motivation on employee performance at the Bitung Fishery Port (2) the influence of the work environment on employee performance at the Bitung Fishery Port (3) the influence of motivation and work environment on employee performance at the Bitung Fishery Port. This research is qualitative research with a quantitative approach. The subjects of this research were 53 employees of the Bitung Ocean Fishing Port. Data collection used questionnaire and observation methods. The data analysis techniques used are simple regression analysis and multiple regression analysis. Based on the research results, the conclusions obtained are (1) there is a positive and significant influence of work motivation on employee performance of 11.7%, (2) the work environment has no effect on employee performance which is associated with the value of Sign = 0.234 > 0.05, (3) There is a positive and significant influence of work motivation and work environment together on employee performance at the Bitung Ocean Fishing Port of 13.3% as indicated by the coefficient of determination R²y (1.2) = 0.133.